Analisis Penanaman Karakter Sopan Santun di Kelas 1 Sekolah Dasar - Darmawan, Agung; Junaidi, Ilham Arvan; Ayurachmawati, Puji (Indonesian Research Journal on Education, 2022)
This research is a qualitative research. The purpose of this study is to describe the cultivation of the polite character of first graders at Al-Alifah Elementary School Palembang, to describesolutions in overcoming these obstacles, and to describe the efforts of classroom teachers inshaping the polite character of first graders. This research was conducted at Al-Alifah Elementary School in Palembang. The data collection technique used is observation. interviewdocumentation The results of this study are 1) The efforts made by the first grade teacher of AlAlifah Palembang elementary school, and greets every meeting with the teacher. 2) the obstacles faced by teachers in character building are lack of confidence in students, with students 3) The solution made by classroom teachers is to teach children with love and attention because as a teacher it is natural be a good example for their students.